2019
DOI: 10.3389/fneur.2018.01129
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Bilateral Secondary Somatosensory Cortex With Right Hand Touch Stimulation: A Meta-Analysis of Functional Neuroimaging Studies

Abstract: Background: Brain regions involved in processing somatosensory information have been well documented through lesion, post-mortem, animal, and more recently, structural and functional neuroimaging studies. Functional neuroimaging studies characterize brain activation related to somatosensory processing; yet a meta-analysis synthesis of these findings is currently lacking and in-depth knowledge of the regions involved in somatosensory-related tasks may also be confounded by motor influences.Objectives: Our Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 122 publications
5
39
0
Order By: Relevance
“…3-2). Situated in the inferior parietal lobe, the supramarginal gyrus is part of the sensory association cortex and is involved in higher-order somatosensory processing (Bodegård et al, 2001;Lamp et al, 2019). At the uncorrected level of p Ͻ 0.001, the right primary somatosensory cortex (S1) was also activated (Table 2-2).…”
Section: Neural Attenuation Of Self-generated Touch Compared With Extmentioning
confidence: 99%
“…3-2). Situated in the inferior parietal lobe, the supramarginal gyrus is part of the sensory association cortex and is involved in higher-order somatosensory processing (Bodegård et al, 2001;Lamp et al, 2019). At the uncorrected level of p Ͻ 0.001, the right primary somatosensory cortex (S1) was also activated (Table 2-2).…”
Section: Neural Attenuation Of Self-generated Touch Compared With Extmentioning
confidence: 99%
“…These control networks were linked to task-negative, social-affective and introspective processes, as well as motor and sensory processes. In particular, the three networks comprised (i) the extended social-affective default network (eSAD; Amft et al, 2015 ), (ii) a combined motor network associated with finger tapping and prosaccade eye movements (Motor + PS; Cieslik et al, 2016 ; Witt et al, 2008 ), and (iii) a combined motor-sensory network linked to finger tapping and hand stimulation/somatosensory processing (Motor + SS; Lamp et al, 2019 ; Witt et al, 2008 ). These motor-sensory systems are strongly interconnected compared to large-scale cognitive networks with transitions between network boundaries, and converge less with fronto-parietal cognitive areas ( Cieslik et al, 2016 ; Fox & Raichle, 2007 ; Yeo et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the OP1 area most likely processes tactile input in general, rather than tactile motion specifically. Evidence for this is that it is activated in response to a variety of tactile stimuli ( Burton et al , 2008 ), and that lesions affecting the parietal operculum are associated with impaired somatosensory processing in tasks that do not require processing of motion cues ( Preusser et al , 2015 ; Meyer et al , 2016 ; Lamp et al , 2019 ). Furthermore, S2 OP1 activation appears unaffected by the performance level on the TDD test ( Lundblad et al , 2011 ), and was still activated during TDD testing in a patient with a spinal cord lesion who, although he reported sensing the tactile stimulus, was unable report movement direction ( Lundblad et al , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ipsilateral impairment in somatosensory function is evident in 20–30% of patients with unilateral brain lesions ( Corkin et al , 1973 ; Connell et al , 2008 ). TDD bilaterally activates S2 and insula ( Lamp et al ., 2019 ; Lundblad et al , 2011 ), and restricted experimental lesions alter cortical processing in widespread areas ( Wahlbom et al , 2019 ). A recent meta-analysis of functional neuroimaging studies of tactile processing of stimulation applied to the hand found bilateral activation in both S2 and the insula ( Lamp et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%